2018
DOI: 10.1007/s13105-018-0636-y
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of lncRNA MALAT1 contributes to renal functional improvement after duodenal-jejunal bypass in a diabetic rat model

Abstract: Ameliorated renal function has been reported after bariatric surgery, but the mechanisms underlying this phenomenon are not well-studied. To investigate whether the long non-coding RNA (lncRNA) MALAT1 mediates the amelioration of diabetic nephropathy after duodenal-jejunal bypass (DJB) surgery, rats were assigned randomly into four groups: diabetic (DM) group, DM with DJB surgery group, DM with sham surgery group, and healthy control group. Food intake, body weight, oral glucose tolerance test (OGTT), urine al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 40 publications
2
25
0
Order By: Relevance
“…35 MALAT1 was also up-regulated in hyperglycemia and involved in hyperglycemia-induced dysfunction of retinal EC. 46 H 2 O 2 induced oxidative injury of ECs and up-regulated the expression of MALAT1. MALAT1 inhibited apoptosis of HUVECs by activating Nrf2 signaling pathway via downregulation of Keap1.…”
Section: The Malat1 and Endothelial Dysfunctionmentioning
confidence: 97%
See 1 more Smart Citation
“…35 MALAT1 was also up-regulated in hyperglycemia and involved in hyperglycemia-induced dysfunction of retinal EC. 46 H 2 O 2 induced oxidative injury of ECs and up-regulated the expression of MALAT1. MALAT1 inhibited apoptosis of HUVECs by activating Nrf2 signaling pathway via downregulation of Keap1.…”
Section: The Malat1 and Endothelial Dysfunctionmentioning
confidence: 97%
“…MiR‐22‐3p targeted CXC chemokine receptor 2, which played a key role in protecting the integrity of the endothelium . MALAT1 was also up‐regulated in hyperglycemia and involved in hyperglycemia‐induced dysfunction of retinal EC . H 2 O 2 induced oxidative injury of ECs and up‐regulated the expression of MALAT1.…”
Section: Malat1 and Vascular Diseasesmentioning
confidence: 99%
“…In addition, specific reduction of renal miR-27a decreases renal fibrosis, and targeting miR-27a may represent a novel therapeutic approach for DN [105]. Besides, Wu et al found that downregulation of MALAT1 could improve renal function after duodenal-jejunal bypass in a diabetic rat model [106]. A recent research showed that silencing of lncRNA-GAS5 alleviated the HG-caused HK-2 cell toxicity [9].…”
Section: Therapeutic Potential Of Ncrna In Dnmentioning
confidence: 99%
“…In DM, EC function can be impaired through several mechanisms, such as an alteration in signaling pathways, excessive oxidative stress, activation of pro-inflammatory factors and protein kinase C, and mitochondrial dysfunction [206]. Most recently, several genome-wide studies have been revealed the correlations of the functional involvement of different lncRNAs in ED and diabetes (Table 5) [55][56][57]67,68,75,79,207,208]. RNCR3 Up-regulated in DM and stimulates DM-induced retinal EC dysfunction through regulating RNCR3/ Kruppel like factor 2 (KLF2)/miR-185-5p pathway [79] One of the most common intergenic lncRNAs, named MALAT1, which is located on chromosome 11q13.1 and 7 kb in size, has been functionally identified and characterized in ED-associated diabetes [55].…”
Section: The Correlations Of Functional Involvement Of Lncrnas In Ed mentioning
confidence: 99%